DynamicMultiProTru: An Adaptive Trust Model for Wireless Sensor Networks - Dogan, Gulustan; Avincan, Koksal; Brown, Ted (IEEE, 2016)
In Wireless Sensor Networks nodes can get un-trusted after initial setup due to different reasons such as low energy, difficult environmental conditions, unexpected attacks, hardware defects. When nodes start sending faulty data, the network creates wrong observations. Errors in data can have severe impacts in wireless sensor networks such as leading to wrong decisions mission critical networks. In our earlier work, we designed an architecture for one-hop WSNs called ProTru[1]. In ProTru a static trust threshold was chosen at the time of deployment. In this work, we redeveloped the algorithm for multi-hop networks in a way that trust thresholds are chosen dynamically. We ran simulations to test the effectiveness of this proposed architecture DynamicProTru.
Keywords: Trust; Wireless Sensor Networks; Dynamic Networks; Adaptive Networks; Computer Science; Engineering